Risk factors for juvenile cybercrime: A meta-analytic review. - Wissink, Inge B.; Standaert, Joyce C.A.; Stams, Geert Jan J.M.; Asscher, Jessica J.; Assink, Mark (Aggression & Violent Behavior, 2023)
So far, most meta-analyses and reviews on juvenile crime risk factors focused on risk factors for traditional crimes. It is unknown, though, whether these risk factors are also relevant for the explanation of cybercrime perpetration. This meta-analytic review aimed to identify risk factors for cyberstalking, hacking, and sexting perpetrated by juveniles. A literature search yielded 48 articles (24 for cyberstalking, 15 for sexting, and 10 for hacking) that produced 903 effect sizes (306 for cyberstalking, 61 for sexting, and 536 for hacking). The results showed similarities, but also differences in risk factors for the three types of cybercrime. Overall, peer factors were found to be important for all three types (deviant peers for cyberstalking and hacking and peer pressure for sexting). Besides, for cyberstalking, previous online and offline perpetration and victimization were significant risk factors. Other small but significant effects for multiple cybercrime types were found for dark personality traits (for cyberstalking and sexting) and high computer preoccupation (for cyberstalking and hacking). Implications for (preventive) intervention are discussed, as well as the need for future research. • First meta-analysis on risk factors for juvenile cyberstalking, sexting and hacking. • Similarities and differences were found in risk factors for the 3 cybercrimes. • Peer factors were important risk factors for all 3 cybercrimes. • Prior perpetration and victimization were important risk factors for cyberstalking. • Dark personality traits and high computer preoccupation were risk factors for multiple cybercrimes.